Willingness of patients with breast cancer in the adjuvant and metastatic setting to use electronic surveys (ePRO) depends on sociodemographic factors, health-related quality of life, disease status and computer skills = Die Bereitschaft zur Nutzung von technikbasierten Erhebungen (ePRO) bei Patientinnen mit Mammakarzinom in der adjuvanten und metastasierten Situation in Abhängigkeit von soziodemografischen Merkmalen, gesundheitsbezogener Lebensqualität, Erkrankungsstatus und Technikskills - Graf, Joachim; Keilmann, Lucia; Wallwiener, Markus (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: Because of the often unfavorable prognosis, particularly for patients with metastases, health-related quality of life is extremely important for breast cancer patients. In recent years, data on patient-relevant endpoints is being increasingly collected electronically; however, knowledge on the acceptance and practicability of, and barriers to, this form of data collection remains limited. Material and Methods: A questionnaire was completed by 96 patients to determine to what extent existing computer skills, disease status, health-related quality of life and sociodemographic factors affect patientsʼ potential willingness to use electronics methods of data collection (ePRO). Results: 52 of 96 (55 %) patients reported a priori that they could envisage using ePRO. Patients who a priori preferred a paper-based survey (pPRO) tended to be older (ePRO 53 years vs. pPRO 62 years; p = 0.0014) and typically had lower levels of education (p = 0.0002), were in poorer health (p = 0.0327) and had fewer computer skills (p = 0.0003). Conclusion: Barriers to the prospective use of ePRO were identified in older patients and patients with a lower quality of life. Given the appropriate conditions with regard to age, education and current health status, opportunities to participate should be provided to encourage patientsʼ willingness to take part and ensure the validity of survey results. Focusing on ease of use of ePRO applications and making applications more patient-oriented and straightforward appears to be the way forward.